Comparison of the effects of different loading locations on stresses transferred to straight and angled implant-supported zirconia frameworks: a finite element method study - Guven, Sedat; Atalay, Yusuf; Asutay, Fatih; Ucan, Musa Can; Dundar, Serkan; Karaman, Tahir; Gunes, Nedim (Taylor & Francis Ltd, 2015)
The paper presents three-dimensional (3D) finite element models of straight and angled implants and their zirconium-based superstructures. The key objective was to compare the influence of different loading conditions on the stress distribution of straight and angled implants and the zirconia frameworks. 3D finite element straight- and angled-implant models of a mandibular section of bone with missing second molars and their zirconium-based superstructures were used. The straight and angled implants were 4.7 x 13-mm screw-type dental implant systems. Total loads of 300 N were applied in a vertical direction and in an oblique (30 degrees to the vertical) direction buccolingually. Maximum and minimum von Mises stress values of the titanium structures (abutment and implant body) and zirconia frameworks were calculated. When the two groups were examined, the highest stress value was in the zirconia framework of the angled implant-supported model with an oblique loading force (731.46 MPa). The lowest stress values were concentrated in the straight implant-supported model. Thus, the stress values in the angled implant-supported crown were higher than those in the straight implant-supported model. Stress values with oblique loading forces were higher than the values with vertical loading forces. The highest stress value in the zirconia framework was similar to the ultimate strength of the zirconia.
Keywords: finite element analysis (FEA); stress distribution; zirconia framework; straight and angled implant; vertical and oblique loading force